The performance of Keretapi Tanah Melayu Berhad (KTMB): analysis based on profitability / Firdaus Ali Mokhtar - Ali Mokhtar, Firdaus (Faculty of Business and Management, 2010)
This study reveals on the important of towards having a good performance based on profitability. From that, the analysis on the profitability performance will be carried out. The reason is because the stability of one company is depending on their profitability performance and how they utilize it for the company benefits. They can operate effectively and efficiently by having good profitability performance. From the financial statement (balance sheet and income statement), the evaluation of the company performance can be done. To analyze the company that involve in this study, the basic tool of financial analysis will be used. The profitability ratios will be calculated based on the information disclosed on the financial statement of the companies. The study identifies the financial strength on certain criteria. There are five types of common profitability ratios will apply to calculate the financial statement such as gross profit margin, net profit margin, operating profit margin, return on asset and return on equity. The determination whether the company doing well in managing their financial activities in the last 5 years can be made by analysis of profitability ratio. An analysis has been given on each of the selected ratios after been calculated. From the ratio, we will know the performance of the company is decrease in year 2008. This is because the cost of good sales of the company is high and affects the company performance. For better performance in the future, the company needs to take some action in order to increase the effectiveness and efficiency of the company.